Modulation of metal surface abrasive tribocleaning - Шевеля, B. B.; Дворук, В. И.; Радченко, A. B. (Proceedings of National Aviation University (archive), 2000)
Considered is the peculiarity of construction of metal surface tribocleaning model with ipplication of statistical method